THE INTONATION STRUCTURE OF ENGLISH: A COMPREHENSIVE ANALYSIS - Ubaydullayeva Sadoqat Sobirjon Qizi; Abduraimova Shabnam Zokirjon Qizi; Eshbo’riyeva Husnora Azamat Qizi (TADQIQOTLAR, 2025)
Abstract Intonation,  the  variation  in  pitch  during  speech,  is  a  fundamental  feature  of English  that  conveys  grammatical  structure,  emotional  nuance,  and  discourse dynamics. This study examines the components, patterns, and functions of intonation in  English  across  various  sentence  types  and  contexts.  Through  corpus  analysis, phonetic transcription, and contextual evaluation, we illustrate how intonation shapes meaning. The findings highlight intonation’s critical role in effective communication, with  implications  for  linguistic  research,  language  teaching,  and  cross-cultural interactions.